Inhibitory effects of tetramethylpyrazine on platelets during cardiopulmonary bypass and arterial thrombus formation in dogs - Wu Guo-Xin; Wu Jin-Chang; Ma Hai-Tao; Ruan Chang-Geng (Acta Pharmacologica Sinica, 2016)
The corrected platelet count at the end of cardiopulmonary bypass (CPB) in nontreated dogs fell to 56.7% of the pre-operative level, while in tetramethylpyrazine (TMP, 10 mg.kg-1, iv)-treated dogs it fell to 82.8%. The number of alpha-granule membrane protein (GMP-140) which was expressed on the surface of activated platelets increased from the outset of CPB and reached the peak at the end of CPB in control dogs. But the number of GMP-140 molecules did not increase significantly throughout the operative procedure in TMP-treated dogs. In experimental thrombosis in dogs, the weight of the thrombus reduced to 23% of that in controls and the radioactivity ratio between the thrombus and blood was only 29% of that in controls at 4 h after iv injection of 125I-SZ-51 (a monoclonal antibody against GMP-140). These results indicate that TMP inhibits the platelet activation during CPB and arterial thrombosis.